Neither Last nor Least Integration of Early Palliative Care Into Standard Oncology Care - Roland Kunz (healthbook TIMES. Oncology Hematology)
Traditionally, medical oncology has concentrated on the development, implementation, and application of anti-cancer therapies, therefore in a number of cancers long- and short-term survival has been significantly improved.^1^ However, for most patients, quality of life is crucial, irrespective of the clinical course of the illness or the duration of survival.^2^ It is estimated that by 2060, over 16 million people will die from malignant neoplasms and experience serious health-related suffering annually, which is double the number compared with 2016.^3^ Consequently, building non-specialist palliative care capacity among all healthcare providers by integration of palliative care in the oncological treatment as early as possible is crucial.^2,4^ But how can we do that?